Green synthesis, characterization and in vitro biological activities of schiff bases derived from 4-amino-5-methyl-3- mercapto-1,2,4-triazoles and its silver complexes (Funded Work) - MD NADEEM MIYAN; DR. VIJAYAKUMAR DURG (International Journal of Pharma and Bio Sciences, 2019)
Microwave-assisted organic synthesis (MAOS) is the study of chemical reactions under the effect of microwave radiation A series of Silver complexes of different Schiff base ligands are derived from New 4-Amino-5-methyl-3-mercapto-1,2,4-triazoles were synthesized under microwave irradiation. The synthesis of Schiff bases under influence of microwave irradiation was found much easier and faster than conventional heating .The 4-Amino-5-methyl-3-mercapto-1,2,4-triazoles Schif base and complexes are characterized using elemental analysis, Fourier-transform infrared spectroscopy (FTIR) and Proton nuclear magnetic resonance (proton NMR, hydrogen-1 NMR, or 1H NMR) spectroscopy. Under microwave irradiation, the yield and purity of synthesized ligand and its silver complexes are high as compare to conventional method. Microwave Irradiation is Eco-friendly, economic and time saving method. The 4-Amino-5-methyl-3-mercapto-1,2,4-triazole and its Schiff Base is Recrystalized in Ethanol Elemental analysis data suggest the stoichiometry of Silver and Schiff base of New 4-Amino-5-methyl-3-mercapto-1,2,4-triazoles to be 1:1 [M: L] ratio formation in complexes. Comparison of the Fourier-transform infrared spectroscopy (FTIR spectra of the Schiff base and metal complexes indicate that the Schiff base functions as bidentate and tridentate ligand coordinated to the metal via the nitrogen, oxygen and sulfur chromophore. Study of antimicrobial activity of the Schiff bases and the metal complexes against some clinically significant bacteria, namely Staphylococcus aureus, Escherichia .coli and antifungal activity against Aspergillus niger and Candida albicans, All the ligands and complexes have found to be anti-microbial activity but lower than the standarded Durg and the antifunfungal activity is studied but their zone of inhibition is not measure.